Case Report: 18F-Fluoro-L-Phenylalanine Positron Emission Tomography Findings and Immunoreactivity for L-Type Amino Acid Transporter 1 in a Dog With Meningioma - Lee, Dohee; Yun, Taesik; Kim, Sanggu; Koo, Yoonhoi; Chae, Yeon; Kim, Soochong; Chang, Dongwoo; Yang, Mhan-Pyo; Kim, Hakhyun; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2022)
A 12-year-old intact female Miniature Pinscher dog weighing 5.4 kg presented with a history of seizures. On neurological examination, postural reactions were decreased in the left-sided limbs, and menace responses were bilaterally absent. Magnetic resonance imaging (MRI) of the brain was performed, and a solitary amorphous mass (2.7 × 1.9 × 2.2 cm) was observed on the right side of the frontal lobe. Based on the signalment, clinical signs, and MRI findings, a brain tumor was tentatively diagnosed, and meningioma was suspected. The dog was treated with hydroxyurea, prednisolone, and other antiepileptic drugs. One week after the treatment began, postural reactions returned to normal, and the menace response improved. At 119 days after treatment, 18F-fluoro-L-phenylalanine (18F-FDOPA) positron emission tomography (PET) was performed. Marked 18F-FDOPA uptake was observed in the lesion. The mean and maximal standardized uptake values of the lesion were 2.61 and 3.72, respectively, and the tumor-to-normal tissue ratio was 1.95. At 355 days after the initial treatment, a second MRI scan was performed and the tumor size had increased to 3.5 × 2.8 × 2.9 cm. The dog died 443 days after the initial treatment and was deﬁnitively diagnosed with grade 1 meningioma by histopathological examination. Immunohistochemical staining for Ki67 and L-type amino acid transporter 1 was positive and negative for p53, respectively. The labeling index of Ki67 was 2.4%. This is the first case to demonstrate 18F-FDOPA PET findings in a clinical case of a dog histologically diagnosed with a meningioma.